2019
DOI: 10.1186/s40168-019-0721-7
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal investigation of the swine gut microbiome from birth to market reveals stage and growth performance associated bacteria

Abstract: Background Despite recent advances in the understanding of the swine gut microbiome at different growth stages, a comprehensive longitudinal study of the lifetime (birth to market) dynamics of the swine gut microbiome is lacking. Results To fill in this gap of knowledge, we repeatedly collected a total of 273 rectal swabs from 18 pigs during lactation (day (d) 0, 11, 20), nursery (d 27, 33, 41, 50, 61), growing (d 76, 90, 104, 116), and finishing (d 130, 146, 159, 174) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

70
301
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 317 publications
(410 citation statements)
references
References 50 publications
(57 reference statements)
70
301
4
1
Order By: Relevance
“…De Filippis et al detected distinct strains of Prevotella copri by metagenome studies and showed that fiber-rich diets were linked to these strains with improved potential for carbohydrate catabolism (27). Broadly, introduction of solid fiber-rich diet to goat before weaning, Prevotella proliferated, which was also observed in other large domestic animals (28). They could be used as potential microbiota to utilize solid diet, maintain rumen community balance and prevent metabolic disease caused by dysbiosis.…”
Section: Discussionsupporting
confidence: 54%
“…De Filippis et al detected distinct strains of Prevotella copri by metagenome studies and showed that fiber-rich diets were linked to these strains with improved potential for carbohydrate catabolism (27). Broadly, introduction of solid fiber-rich diet to goat before weaning, Prevotella proliferated, which was also observed in other large domestic animals (28). They could be used as potential microbiota to utilize solid diet, maintain rumen community balance and prevent metabolic disease caused by dysbiosis.…”
Section: Discussionsupporting
confidence: 54%
“…Thus, the increased presence of Streptococcus in the HZ group may help alleviate stress leading to improved growth performance of weaned piglets. Interestingly, bacterial features associated with Streptococcus were also identified as growth-promoting bacteria in pigs in two recent studies [43,62]. Additionally, a low gut relative abundance of Streptococcus was tied to low body weight piglets compared to a high relative abundance found in those of normal body weight [63].…”
Section: Discussionmentioning
confidence: 95%
“…DNA concentration was measured by a NanoDrop One (Thermo Fisher Scientific, Madison, WI, USA) and diluted to 10 ng/µL. 16S rRNA gene libraries were constructed as described previously [42,43]. Briefly, the V4 region of 16S rRNA from each sample was amplified using the forward primer (5 -GTGCCAGCMGCCGCGGTAA-3 ) and reverse primer (5 -GGACTACHVGGGTWTCTAAT-3 ) with attaching Illumina sequencing primer and barcode sequence.…”
Section: Gut Microbiota Analysesmentioning
confidence: 99%
“…Associated with clinical and growth outcomes, fecal microbiota was evaluated as a main target for these alternative diets. Many authors have described the great impact of early-life events in mammals, and particularly in pigs, on their future health by shaping immune system development through changes in the pattern of microbial intestinal colonization [44,45]. Several works have demonstrated that aging involves greater richness and alpha diversity in the gut, and in the specific case of pig microbiota, the ecosystem has been described as becoming more homogenous between animals (reduced beta diversity) with age as of weaning [46][47][48].…”
Section: Discussionmentioning
confidence: 99%